In situ and ex situ carbon coated Zn2SnO4 nanoparticles as promising negative electrodes for Li-ion batteries. Issue 82 (5th September 2015) - Yuvaraj, Subramanian; Lee, Won Jong; Lee, Chang Woo; Selvan, Ramakrishnan Kalai
<x xml:space="preserve">Abstract</x> Zinc stannate, Zn2SnO4 nanoparticles are successfully synthesized by a facile hydrothermal method.